Advance Fundraising Techniques: An Evidence from Non-Profit Organizations - Maqbool, Nadeem; Razzaq, Shazma; Ul Hameed, Waseem; Nawaz, Muhammad Atif; Niaz, Shafqat Ali (Pakistan Journal of Humanities and Social Sciences, 2019)
The purpose of this research study is to explore the advance fundraising techniques in the non-profit, charitable, philanthropic organizations for the purpose of fundraising. This research study completed on the basis of primary data that is taken from NGO’s in the region of Punjab. Frequency distribution statistical technique is used in this research paper for analyzing the data. Data collection was completed through questionnaire, face to face interviews, telephonic interviews, survey through e-mails from the presidents of the non-profit organization and members of NGO which are working in the Punjab region. NGO’s such as Alpine Welfare, Umeed Welfare, People Woman Welfare Organization, Human development Form etc. were contacted for data collection. Fundraising is the management function. After the research we would be able to understand the advance fundraising techniques and methods. We have found the positive impact of technological media like YouTube, Face book, Twitter, and TV campaigns on the fundraising. In this research it is found that how donor’s relationship can create for fundraising. This research helps to the fundraiser for the fund generating. It gives a way to nonprofit charitable organization to increase their worth of money. The application of this research provides fundraising managers that is the good for any organization profitable or nonprofit able organizations.